PEMANFAATAN TANAMAN UNTUK MENINGKATKAN DAYA TAHAN TUBUH DI DESA TATAH LAYAP, MARTAPURA, KALIMANTAN SELATAN - Erna Prihandiwati; Aulia Rahim (Jurnal Bakti untuk Negeri, 2021)
Covid-19 has become a worldwide disease. Not only developing countries but also developed countries are also affected by the Covid-19 pandemic, including Indonesia. Indonesia, with a high population density and abundant natural resources, is a measure in itself. The population density, which makes Covid-19 transmission vulnerable and the abundance of natural resources, is a potential that must be exploited in overcoming the pandemic through plants that can be used to increase the body's resistance around the place of residence. This activity aims to provide knowledge to the public about the use of plants to increase endurance, especially during the Covid-19 pandemic. The method used in this activity was to form a team of extension agents to give lectures and questions and answers accompanied by leaflets. As a result of this activity, the community has gained a good understanding of plants that can be used to increase endurance and a simple processing process to use the plants around their dwellings to become immune enhancers.